Como se cuidan los dinosaurios? - Yolen, Jane; Teague, Mark; Lombana, Pablo (New York, NY : Scholastic Inc., 2015)
A young dinosaur takes precautions in order to stay safe throughout the day, both at home and at play.
Spanish translation.
Keywords: Dinosaurs -- Juvenile fiction; Dinosaurios -- Novela juvenil